2018
DOI: 10.1002/jum.14716
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Injured Ankle Ligaments on Ultrasonography With Magnetic Resonance Imaging Correlation

Abstract: Ultrasonography (US) has been increasingly used in the evaluation of ankle ligamentous injuries given its advantages as a dynamic, efficient, noninvasive, and cost-effective imaging method. Understanding the anatomy of the ankle ligaments is critical for correct diagnosis and treatment. This pictorial essay describes and illustrates the US scanning technique and potential pitfalls in evaluating the ankle ligaments and also provides an overview of the US appearance of normal and injured ankle ligaments with mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In addition, MDC values for the SL dimensions, such as length (MDC US = 0.069 cm versus MDC Caliper = 0.083 cm), thickness (MDC US = 0 cm versus MDC Caliper = 0.021 cm) and width (MDC US = 0.013 cm versus MDC Caliper = 0 cm), showed that US measurements presented a higher absolute accuracy with lower MDC values than caliper measures for SL length and thickness dimensions, while caliper displayed greater absolute accuracy with lower MDC for SL width dimensions. According to MDC may be used as the change magnitude necessary to provide measuring confidence to be sure about these values are not the result secondary random variations or measurement errors 12 , these MDCs may be considered as cut-off reference values to determine SL dimensions modifications secondary to anatomic abnormalities 58 , ultrasound-guided invasive procedures 9 , and ligament injuries course after treatment 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MDC values for the SL dimensions, such as length (MDC US = 0.069 cm versus MDC Caliper = 0.083 cm), thickness (MDC US = 0 cm versus MDC Caliper = 0.021 cm) and width (MDC US = 0.013 cm versus MDC Caliper = 0 cm), showed that US measurements presented a higher absolute accuracy with lower MDC values than caliper measures for SL length and thickness dimensions, while caliper displayed greater absolute accuracy with lower MDC for SL width dimensions. According to MDC may be used as the change magnitude necessary to provide measuring confidence to be sure about these values are not the result secondary random variations or measurement errors 12 , these MDCs may be considered as cut-off reference values to determine SL dimensions modifications secondary to anatomic abnormalities 58 , ultrasound-guided invasive procedures 9 , and ligament injuries course after treatment 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study supported an ultrasound technical study for SL dimensions evaluations compared with caliper measures as gold standard which may be used as a reference for ultrasound-guided procedures in formaldehyde-embalmed human cadavers 9 . Future studies should consider these procedures in fresh-frozen cadavers as well as in vivo with healthy subjects and SL injured patients 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Opposed to MRI, by conducting Ultrasound for patients with acute ligament injury, not only could the edema and coarsening of ligament, abnormal signal in ligament (low signal, high signal, blood ow signal, etc. ), ligament relaxation after rupture and avulsion fracture accompanying with Ligament insertion rupture, be obviously observed, but also Ultrasound has the advantages of dynamic observation and high speci city [10].As a consequence, it can be widely used in preoperative diagnosis of acute and chronic ankle injuries. So in recent years, more and more scholars have adopted Ultrasound for the diagnosis of ankle ligament injury [11].…”
Section: The Diagnosis Of Acute Degree Injury Of Lateral Ankle Ligamementioning
confidence: 99%
“…With this background, for the evaluation of the ATFL and CFL injuries, ankle US imaging could be an option with higher priority due to its lack of radiation, and cost- and time-effectiveness (10). However, previous US evaluation studies regarding ATFL and CFL injuries have shown varied results.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) does not use radiation and is useful in imaging soft tissue, including ligament, tendon, and muscle, bleeding, and swelling; therefore, MRI may be used in a variety of soft tissue abnormalities, including ankle injuries. However, MRI is relatively expensive, time-consuming, and needs a fixed position to acquire images (10).…”
Section: Introductionmentioning
confidence: 99%